2007
DOI: 10.1007/bf03027807
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical analysis of the microbiologically influenced corrosion of steels by sulfate-reducing bacteria

Abstract: The differences between the general corrosion and microbiologically influenced corrosion (MIC) of steels were investigated in terms of its electrochemical behavior and surface phenomena. The corrosion potential of steels in the absence of SRB (sulfate-reducing bacteria) shifted to a negative value with the immersion time. However, the potential of the presence of SRB shifted to a positive value after 30 days' incubation, indicating the growth of SRB biofilms on the test metal specimens and the formation of cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…The steel samples in the sterile groundwater exhibited nobler potentials ( E OCP ) than those in the SRB inoculated medium (Figure 2). The E OCP of steel is associated with samples’ surface states, which include: adsorbed ions, corrosion products and biofilms [25,26]. Meanwhile, the E OCP of the insulated sample in the sterile medium was in the pseudo-passive region during the early stages indicating less corrosion reactions on the steel surface (Figure 2).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The steel samples in the sterile groundwater exhibited nobler potentials ( E OCP ) than those in the SRB inoculated medium (Figure 2). The E OCP of steel is associated with samples’ surface states, which include: adsorbed ions, corrosion products and biofilms [25,26]. Meanwhile, the E OCP of the insulated sample in the sterile medium was in the pseudo-passive region during the early stages indicating less corrosion reactions on the steel surface (Figure 2).…”
Section: Resultsmentioning
confidence: 99%
“…The insulated sample in the sterile medium exhibited the lowest corrosion rate during the test due to the limited diffusion of corrosive species across the insulation, evidenced by the Warburg coefficient (Table 1). In comparison, the samples in the sterile medium presented lower corrosion rates than those in the SRB inoculated medium, which indicates that the corrosion products film protected the steel surface to some extent in the absence of SRB [25,26].
Figure 6 Evolution of linear polarisation resistance ( R LPR ) with immersion period for the insulated and uninsulated steel samples tested in the sterile and SRB inoculated media.
…”
Section: Resultsmentioning
confidence: 99%
“…[ 6 ] SRB were defined as the notorious corrosion‐enhancing anaerobic microorganisms that are ubiquitous in the natural environment. [ 7,8 ] MIC induced by SRB has been extensively investigated in the literature. Zhu et al [ 9 ] found that the corrosion rate of X56 steel in the sea mud containing SRB was 10‐fold higher than that in the sea mud without SRB.…”
Section: Introductionmentioning
confidence: 99%